Alloy powder composition and inductor
Patent Information
- Application Number
- CN202610334644.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-03-24
- Filing Date
- 2026-03-18
- Publication Date
- 2026-09-25
Smart Images

Figure CN122822531A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to an alloy powder composition and an inductor, and more particularly to an alloy powder composition comprising three magnetic powders and an inductor. Background Technology
[0002] Existing electronic devices, such as smartphones, typically have magnetic components, such as inductors. Many of these magnetic components are made from alloy powder compositions, which sometimes need to have high packing density, high magnetic permeability, and low core loss to meet the requirements of some electronic devices. Summary of the Invention
[0003] The alloy powder composition provided by this invention comprises three types of magnetic powders, each of which includes an amorphous alloy, a nanocrystalline alloy, a crystalline alloy, and / or pure iron powder. The alloy powder composition of this invention has high packing density, high permeability, and low magnetic loss, which is beneficial for improving the efficiency and high-frequency performance of inductors, and for enhancing power conversion efficiency.
[0004] At least one embodiment of the present invention provides an alloy powder composition. Based on 100% by weight of the total weight of the alloy powder composition, the alloy powder composition comprises 5% to 90% by weight of a first magnetic powder, 5% to 90% by weight of a second magnetic powder, and 5% to 90% by weight of a third magnetic powder. The first magnetic powder comprises a first amorphous alloy, a first nanocrystalline alloy, or a first crystalline alloy. The second magnetic powder comprises a second amorphous alloy, a second nanocrystalline alloy, or a second crystalline alloy. The third magnetic powder comprises pure iron powder or a third crystalline alloy.
[0005] In some embodiments, the first crystalline alloy comprises a first iron-silicon-chromium alloy, a first iron-silicon-aluminum alloy, a first iron-silicon alloy, a first iron-silicon-chromium-aluminum alloy, or a first iron-silicon-chromium-nickel alloy. In some embodiments, the second crystalline alloy comprises a second iron-silicon-chromium alloy, a second iron-silicon-aluminum alloy, a second iron-silicon alloy, a second iron-silicon-chromium-aluminum alloy, or a second iron-silicon-chromium-nickel alloy. In some embodiments, the third crystalline alloy comprises an iron-nickel alloy, a third iron-silicon-chromium alloy, a third iron-silicon-aluminum alloy, or a third iron-silicon alloy.
[0006] In some embodiments, the alloy powder composition comprises 10 to 80 wt% of a first magnetic powder, 10 to 80 wt% of a second magnetic powder, and 10 to 80 wt% of a third magnetic powder.
[0007] In some embodiments, the alloy powder composition comprises 10 to 60 wt% of a first magnetic powder, 20 to 70 wt% of a second magnetic powder, and 20 to 70 wt% of a third magnetic powder.
[0008] In some embodiments, the alloy powder composition comprises 10 to 40 wt% of a first magnetic powder, 20 to 40 wt% of a second magnetic powder, and 20 to 70 wt% of a third magnetic powder.
[0009] In some embodiments, the median particle size D50 of the first magnetic powder is 2 μm to 36 μm, the median particle size D50 of the second magnetic powder is 2 μm to 35 μm, and the median particle size D50 of the third magnetic powder is 0.5 μm to 15 μm.
[0010] In some embodiments, the density of the alloy powder composition is 5 g / cm³. 3 Up to 8g / cm 3 .
[0011] In some implementations, under test conditions at a frequency of 1 MHz, the relative permeability (μ) of the alloy powder composition is... r The range is 10 to 70.
[0012] In some embodiments, under test conditions of 1 MHz frequency and 30 mT magnetic flux density amplitude, the magnetic loss of the alloy powder composition is 200 kW / m. 3 Up to 1500kW / m 3 .
[0013] In some embodiments, the Vickers hardness of the first magnetic powder is from 300 MPa to 700 MPa. In some embodiments, the Vickers hardness of the second magnetic powder is from 300 MPa to 700 MPa. In some embodiments, the Vickers hardness of the third magnetic powder is from 100 MPa to 450 MPa.
[0014] At least one embodiment of the present invention provides an inductor. The inductor includes a magnetically conductive layer and conductive lines disposed in the magnetically conductive layer, wherein the magnetically conductive layer comprises the aforementioned alloy powder composition. Attached Figure Description
[0015] The features of the invention will be fully understood when read in conjunction with the accompanying drawings. It should be noted that, according to industry standard practice, the features are not drawn to scale and are for illustrative purposes only. In fact, the dimensions of the features may be increased or decreased arbitrarily for clarity of explanation.
[0016] Figure 1 This is a three-dimensional schematic diagram of an inductor according to some embodiments of the present invention.
[0017] Figure 2 For along Figure 1 A schematic diagram of the cross section A-A'. Detailed Implementation
[0018] In this invention, the range expressed as "from one value to another" is a concise way of representing a range to avoid listing all the values within that range in the specification. Therefore, the description of a particular range of values encompasses any value within that range as well as the smaller range of values defined by that value, as if the arbitrary value and the smaller range of values were explicitly stated in the specification. As used in this invention, the term "and / or" includes any and all combinations of one or more of the associated listed items.
[0019] It is understood that although terms such as "first" and "second" may be used here to describe various elements, these elements should not be limited by these terms. These terms are only used to distinguish one element from another. For example, without departing from the scope of the embodiments, a first element may be referred to as a second element, and similarly, a second element may be referred to as a first element.
[0020] Additionally, when numbers or ranges are described as “approximately,” “about,” “substantially,” and other similar terms, this is to cover numbers described as falling within a reasonable range, as those skilled in the art will understand to be within + / - 10%. For example, the term “approximately 5 μm” covers a size range from 4.5 μm to 5.5 μm.
[0021] Currently, an alloy powder composition containing two magnetic powders is known; however, this binary alloy powder composition suffers from problems such as low packing density, low permeability, and high magnetic loss. This invention discloses a ternary alloy powder composition containing three magnetic powders. Compared to traditional binary alloy powder compositions, the ternary alloy powder composition of this invention has high packing density, high permeability, and low magnetic loss. Furthermore, compared to traditional binary alloy powder compositions, the ternary alloy powder composition of this invention includes an additional magnetic powder, whose materials and proportions can be adjusted according to requirements to further refine the inductor's characteristics.
[0022] This invention provides an alloy powder composition. Based on 100% by weight of the total weight of the alloy powder composition, the composition comprises 5% to 90% by weight of a first magnetic powder, 5% to 90% by weight of a second magnetic powder, and 5% to 90% by weight of a third magnetic powder. The first magnetic powder comprises a first amorphous alloy, a first nanocrystalline alloy, or a first crystalline alloy. The second magnetic powder comprises a second amorphous alloy, a second nanocrystalline alloy, or a second crystalline alloy. The third magnetic powder comprises pure iron powder or a third crystalline alloy.
[0023] It should be noted that the "amorphous alloy," "nanocrystalline alloy," and "crystalline alloy" of this invention are all soft magnetic materials. The "amorphous alloy" of this invention prevents crystal nucleation during solidification through rapid cooling or alloy design, maintaining a short-range ordered, long-range disordered solid metal structure in the solid state. Because the atomic arrangement of amorphous alloys is disordered and irregular, the grain size cannot be directly observed. The "nanocrystalline alloy" of this invention is composed of ultrafine grains, which are typically formed by the nucleation and growth of amorphous precursor alloys at appropriate annealing temperatures. Nanoscale magnetic crystals (α-Fe) can precipitate in the amorphous alloy, with (α-Fe) crystal sizes ranging from approximately 1 nm to approximately 100 nm, and common grain sizes ranging from approximately 10 nm to approximately 20 nm. Compared to traditional crystalline metals, nanocrystalline alloys exhibit superior performance, including high permeability, high saturation flux density, low coercivity, and low iron loss. The crystals of the "crystalline alloy" of the present invention are arranged in a long-range ordered manner, and the size of the crystals is between several hundred nm and several mm.
[0024] In some embodiments, the first crystalline alloy comprises a first iron-silicon-chromium alloy, a first iron-silicon-aluminum alloy, a first iron-silicon alloy, a first iron-silicon-chromium-aluminum alloy, or a first iron-silicon-chromium-nickel alloy. In some embodiments, the second crystalline alloy comprises a second iron-silicon-chromium alloy, a second iron-silicon-aluminum alloy, a second iron-silicon alloy, a second iron-silicon-chromium-aluminum alloy, or a second iron-silicon-chromium-nickel alloy. In some embodiments, the third crystalline alloy comprises an iron-nickel alloy, a third iron-silicon-chromium alloy, a third iron-silicon-aluminum alloy, or a third iron-silicon alloy.
[0025] It is understood that the compositions of the "first iron-silicon-chromium alloy," "second iron-silicon-chromium alloy," and "third iron-silicon-chromium alloy" of the present invention may be the same or similar. The compositions of the "first iron-silicon-aluminum alloy," "second iron-silicon-aluminum alloy," and "third iron-silicon-aluminum alloy" of the present invention may be the same or similar. The compositions of the "first iron-silicon alloy," "second iron-silicon alloy," and "third iron-silicon alloy" of the present invention may be the same or similar. The compositions of the "first iron-silicon-chromium-aluminum alloy" and "second iron-silicon-chromium-aluminum alloy" of the present invention may be the same or similar. The compositions of the "first iron-silicon-chromium-nickel alloy" and "second iron-silicon-chromium-nickel alloy" of the present invention may be the same or similar. The alloy compositions and their contents of the present invention are shown in Table 1 below, where the unit is weight percentage (wt%), but are not limited to these alloy compositions and their contents.
[0026] Table 1
[0027] In some embodiments, the first magnetic powder comprises 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, or 85% by weight in the alloy powder composition. If the content of the first magnetic powder is less than 5% by weight, the resulting alloy powder composition has low magnetic permeability and high magnetic loss. If the content of the first magnetic powder is greater than 90% by weight, the molding compaction density is low, and the resulting alloy powder composition has low packing density and low magnetic permeability.
[0028] In some embodiments, the second magnetic powder comprises 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, or 85% by weight in the alloy powder composition. If the content of the second magnetic powder is less than 5% by weight, the resulting alloy powder composition has low magnetic permeability and high magnetic loss. If the content of the second magnetic powder is greater than 90% by weight, the molding compaction density is low, and the resulting alloy powder composition has low packing density and low magnetic permeability.
[0029] In some embodiments, the third magnetic powder comprises 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, or 85% by weight in the alloy powder composition. If the content of the third magnetic powder is less than 5% by weight, the resulting alloy powder composition has low permeability and high magnetic loss. If the content of the third magnetic powder is greater than 90% by weight, the molding compaction density is low, and the resulting alloy powder composition has low packing density and low permeability. In some embodiments, when the third magnetic powder comprises at least 6% by weight, it is advantageous to obtain the alloy powder composition of the present invention, which has high packing density, high permeability, and low magnetic loss.
[0030] In some specific embodiments, the alloy powder composition is composed of 5 to 90% by weight of a first magnetic powder, 5 to 90% by weight of a second magnetic powder, and 5 to 90% by weight of a third magnetic powder, based on a total weight percentage of 100%.
[0031] In some specific embodiments, the alloy powder composition is composed of 10% to 80% by weight of a first magnetic powder, 10% to 80% by weight of a second magnetic powder, and 10% to 80% by weight of a third magnetic powder, based on a total weight percentage of 100%.
[0032] In some specific embodiments, the alloy powder composition is composed of 10% to 60% by weight of a first magnetic powder, 20% to 70% by weight of a second magnetic powder, and 20% to 70% by weight of a third magnetic powder, based on a total weight percentage of 100%.
[0033] In some specific embodiments, the alloy powder composition, based on 100% by weight of the total weight of the alloy powder composition, consists of 10% to 40% by weight of a first magnetic powder, 20% to 40% by weight of a second magnetic powder, and 20% to 70% by weight of a third magnetic powder. When the content of the alloy powder composition is within the above range, the alloy powder composition has high bulk density, high permeability, and low magnetic loss.
[0034] In some embodiments, the median particle size D50 of the first magnetic powder is from 2 μm to 36 μm, for example, 4 μm, 4.5 μm, 6 μm, 6.5 μm, 7 μm, 8 μm, 9 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 22 μm, 23 μm, 26 μm, 30 μm, 32 μm, or 34 μm. In some embodiments, the decimal particle size D10 of the first magnetic powder is from 2 μm to 10 μm, for example, 4 μm, 6 μm, or 8 μm. In some embodiments, the decimal particle size D90 of the first magnetic powder is from 8 μm to 65 μm, for example, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, or 60 μm.
[0035] In some embodiments, the median particle size D50 of the second magnetic powder is from 2 μm to 35 μm, for example, 3.5 μm, 4 μm, 4.5 μm, 6 μm, 6.5 μm, 8 μm, 10 μm, 11 μm, 12 μm, 15 μm, 16 μm, 17 μm, 18 μm, 20 μm, 21 μm, 23 μm, 26 μm, 28 μm, 30 μm, 32 μm, or 34 μm. In some embodiments, the decimal particle size D10 of the second magnetic powder is from 2 μm to 10 μm, for example, 4 μm, 6 μm, or 8 μm. In some embodiments, the decimal particle size D90 of the second magnetic powder is from 8 μm to 65 μm, for example, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, or 60 μm. In some embodiments, the particle size of the first magnetic powder may be greater than, equal to or smaller than the particle size of the second magnetic powder.
[0036] In some embodiments, the median particle size D50 of the third magnetic powder is from 0.5 μm to 15 μm, for example, 0.9 μm, 1.5 μm, 2 μm, 3.5 μm, 4 μm, 5 μm, 6 μm, 6.5 μm, 7 μm, 8 μm, 10 μm, or 12 μm. In some embodiments, the decimal particle size D10 of the third magnetic powder is from 0.5 μm to 3.5 μm, for example, 1 μm, 2 μm, or 3 μm. In some embodiments, the decimal particle size D90 of the third magnetic powder is from 1 μm to 16 μm, for example, 2 μm, 4 μm, 6 μm, 8 μm, 10 μm, 12 μm, or 14 μm.
[0037] It is worth noting that the third magnetic powder has a smaller particle size compared to the first and second magnetic powders. Therefore, the third magnetic powder can fill the gaps between the first and second magnetic powders, thereby increasing the packing density of the alloy powder composition, further improving its permeability, and reducing its magnetic loss. Thus, when the median particle size D50 of the first, second, and third magnetic powders is within the aforementioned range, it is advantageous to obtain the alloy powder composition of this invention, which has high packing density, high permeability, and low magnetic loss.
[0038] In an embodiment of the present invention, the alloy powder composition is subjected to a pressure forming step to form a T18 ring core, wherein the T18 ring core has an outer diameter of about 18 mm, an inner diameter of about 10 mm, and a maximum height of about 5 mm.
[0039] In some embodiments, the density of the alloy powder composition is 5 g / cm³. 3 Up to 8g / cm 3For example, 5.2, 5.4, 5.5, 5.6, 5.8, 6, 6.2, 6.3, 6.35, 6.4, 6.5, 6.6, 6.8, 7, 7.2, 7.4, 7.5, 7.6, or 7.8 g / cm³ 3 When the density of the alloy powder composition falls within the aforementioned range, it is advantageous to obtain the alloy powder composition of this invention, which exhibits high magnetic permeability and low magnetic loss. The density of this invention is measured for the T18 toroidal core using a geometric method or ASTM (American Society for Testing and Materials) B962, where ASTM B962 employs the Archimedes method. The density of the T18 toroidal core is calculated by dividing the core mass by the core volume.
[0040] In some embodiments, under test conditions at a frequency of 1 MHz, the relative permeability (μ) of the alloy powder composition is... r The relative permeability of the T18 toroidal core is between 10 and 70, for example, 20, 22, 24, 26, 28, 30, 32, 33, 34, 35, 36, 37, 38, 39, 40, 42, 43, 44, 46, 48, 50, 52, 54, 56, 58, 60, 62, 64, 65, 66, or 68. The relative permeability of this invention is calculated by measuring the T18 toroidal core according to IEC (International Electrotechnical Commission) 62044-2, resulting in the effective permeability (μ). e ) and relative permeability.
[0041] In some embodiments, under test conditions of 1 MHz frequency and 30 mT magnetic flux density amplitude, the magnetic loss of the alloy powder composition is 200 kW / m. 3 Up to 1500kW / m 3 For example, 300, 400, 500, 600, 700, 750, 800, 850, 900, 950, 1000, 1100, 1200, 1300 or 1400 kW / m 3 The magnetic loss of the present invention is measured on a T18 toroidal core using a BH instrument in accordance with IEC 62044-3.
[0042] In some embodiments, the Vickers hardness (HV) of the first magnetic powder is 300 MPa to 700 MPa, for example, 400 MPa, 500 MPa, or 600 MPa. In some embodiments, the Vickers hardness of the second magnetic powder is 300 MPa to 700 MPa, for example, 400 MPa, 500 MPa, or 600 MPa. In some embodiments, the Vickers hardness of the third magnetic powder is 100 MPa to 450 MPa, for example, 200 MPa, 300 MPa, or 400 MPa. In some embodiments, the Vickers hardness of the third magnetic powder is less than or equal to the Vickers hardness of the first magnetic powder and the Vickers hardness of the second magnetic powder. When the Vickers hardness of the three magnetic powders is within the above range, it is beneficial to increase the packing density of the alloy powder composition, thereby increasing the permeability and reducing magnetic loss. The Vickers hardness of the present invention is measured using a nanoindentation testing machine to measure the first to third magnetic powders respectively.
[0043] The method for manufacturing the alloy powder composition of the present invention is as follows. First, a first magnetic powder, a second magnetic powder, and a third magnetic powder are mixed. Then, the three magnetic powders are uniformly mixed with additives and a colloid to obtain a magnetic powder mixture. After the magnetic powder mixture undergoes a wet sieving granulation step, it is then subjected to a drying step and a dry sieving granulation step to obtain the alloy powder composition of the present invention.
[0044] Figure 1 This is a perspective view of an inductor 100 according to some embodiments of the present invention. Please refer to... Figure 1 The inductor 100 includes a body 110 and external electrodes 120 and 130. The external electrodes 120 and 130 are respectively disposed at both ends of the body 110.
[0045] Figure 2 For along Figure 1 A cross-sectional view along section A-A'. Please refer to the diagram. Figure 2 The inductor 100 includes a magnetically conductive layer M and conductive lines L disposed in the magnetically conductive layer M, wherein the magnetically conductive layer M comprises the aforementioned alloy powder composition. The alloy powder composition may, for example, be a core material used in inductors. It should be noted that... Figure 1 and Figure 2 The inductor 100 is only one embodiment, and the alloy powder composition of the present invention is not limited to its application in the inductor 100.
[0046] The following experimental results using multiple embodiments and comparative examples are used to illustrate the technical content and effects of the embodiments of the present invention in more detail, but they are not intended to limit the present invention.
[0047] Comparative Example 1 and Comparative Example 2 Please refer to Table 2 below. The binary alloy powder composition in Comparative Example 1 contains 30 wt% amorphous alloy and 70 wt% pure iron. The alloy powder composition in Comparative Example 2 contains 45 wt% amorphous alloy, 50 wt% nanocrystalline alloy, and 5 wt% iron-silicon-chromium alloy.
[0048] Since the alloy powder composition of Comparative Example 1 contains only two kinds of magnetic powder, its crystal content is low and its pure iron content is high. Therefore, the measured relative permeability is low and the magnetic loss is high.
[0049] Table 2
[0050] Experimental Examples 1 to 6 Please refer to Table 3 below. The same first to third magnetic powders were used in Experiments 1 to 3, and their materials and median particle size D50 were the same. Since Experiments 1 to 3 used different contents of the first to third magnetic powders, the resulting densities, relative permeability, and magnetic losses were also different.
[0051] The relative permeability and magnetic loss of the alloy powder compositions in Experimental Examples 1 to 6 are superior to those in Comparative Examples 1 and 2. Therefore, the alloy powder compositions of the present invention are beneficial for improving the efficiency and high-frequency performance of inductors and for enhancing power conversion efficiency.
[0052] Table 3
[0053] Experimental Examples 7 to 11 Please refer to Table 4 below. The relative permeability and magnetic loss of the alloy powder compositions in Experimental Examples 7 to 11 are superior to those in Comparative Examples 1 and 2. Therefore, the alloy powder compositions of the present invention are beneficial for improving the efficiency and high-frequency performance of inductors, and for improving power conversion efficiency.
[0054] Table 4
[0055] In summary, the alloy powder composition provided by this invention comprises three types of magnetic powders, each of which includes an amorphous alloy, a nanocrystalline alloy, a crystalline alloy, and / or pure iron powder. The alloy powder composition of this invention exhibits high packing density, high permeability, and low magnetic loss, which is beneficial for improving the efficiency and high-frequency performance of inductors, and for enhancing power conversion efficiency.
[0056] Although the present invention has been disclosed above by way of embodiments, it is not intended to limit the disclosed content. Those skilled in the art can make various modifications and refinements without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention shall be determined by the appended claims.
[0057] [Symbol Explanation] 100: Inductor 110: Ontology 120, 130: External electrodes A-A': section line L: Conductive circuit M: Magnetic layer.
Claims
1. An alloy powder composition, characterized in that, Based on the total weight of the alloy powder composition as 100% by weight, it comprises: The first magnetic powder comprises 5% to 90% by weight, wherein the first magnetic powder comprises a first amorphous alloy, a first nanocrystalline alloy, or a first crystalline alloy. A second magnetic powder, comprising 5 to 90% by weight, wherein the second magnetic powder comprises a second amorphous alloy, a second nanocrystalline alloy, or a second crystalline alloy; and The third magnetic powder comprises 5% to 90% by weight, wherein the third magnetic powder contains pure iron powder or a third crystalline alloy.
2. The alloy powder composition according to claim 1, characterized in that, in: The first crystalline alloy comprises a first iron-silicon-chromium alloy, a first iron-silicon-aluminum alloy, a first iron-silicon alloy, a first iron-silicon-chromium-aluminum alloy, or a first iron-silicon-chromium-nickel alloy. The second crystalline alloy comprises a second iron-silicon-chromium alloy, a second iron-silicon-aluminum alloy, a second iron-silicon alloy, a second iron-silicon-chromium-aluminum alloy, or a second iron-silicon-chromium-nickel alloy, and The third crystalline alloy includes an iron-nickel alloy, a third iron-silicon-chromium alloy, a third iron-silicon-aluminum alloy, or a third iron-silicon alloy.
3. The alloy powder composition according to claim 1, characterized in that, in: The first magnetic powder comprises 10 to 80 percent by weight; The second magnetic powder comprises 10 to 80% by weight; and The third magnetic powder accounts for 10 to 80% by weight.
4. The alloy powder composition according to claim 1, characterized in that, in: The first magnetic powder comprises 10 to 60 percent by weight; The second magnetic powder comprises 20 to 70 percent by weight; and The third magnetic powder accounts for 20 to 70 percent by weight.
5. The alloy powder composition according to claim 1, characterized in that, in: The first magnetic powder comprises 10 to 40 percent by weight; The second magnetic powder comprises 20 to 40 percent by weight; and The third magnetic powder accounts for 20 to 70 percent by weight.
6. The alloy powder composition according to claim 1, characterized in that, in: The median particle size D50 of the first magnetic powder is 2 μm to 36 μm; The median particle size D50 of the second magnetic powder is 2 μm to 35 μm; and The median particle size D50 of this third magnetic powder is 0.5 μm to 15 μm.
7. The alloy powder composition according to claim 1, characterized in that, The density of the alloy powder composition is 5 g / cm³. 3 Up to 8g / cm 3 .
8. The alloy powder composition according to claim 1, characterized in that, Under test conditions at a frequency of 1 MHz, the relative permeability of the alloy powder composition ranges from 10 to 70.
9. The alloy powder composition according to claim 1, characterized in that, Under test conditions of 1 MHz frequency and 30 mT magnetic flux density amplitude, the magnetic loss of the alloy powder composition was 200 kW / m. 3 Up to 1500kW / m 3 .
10. The alloy powder composition according to claim 1, characterized in that, in: The Vickers hardness of the first magnetic powder is 300 MPa to 700 MPa; The Vickers hardness of the second magnetic powder is 300 MPa to 700 MPa; and The Vickers hardness of this third magnetic powder is 100 MPa to 450 MPa.
11. An inductor, characterized in that, Include: The magnetic conductive layer comprises the alloy powder composition according to any one of claims 1 to 10; and The conductive lines are disposed within the magnetically conductive layer.